An Analysis of Teachers Perspective in Online English Teaching - Sapariah; Rona Elfiza; Dewi Nopita (Juliet, 2022)
This study aimed to know how is teachers’ perspective in online English teaching at SMPN 10 Tanjungpinang. The subject in this research is the English teacher consists of 3 teachers. This study based on Sri Hariyati theory (2020). A research desgin in this research is descriptive qualitative with analysis technique. The setting of place in this research is at SMPN 10 Tanjungpinang. The instrumens in collecting the data are interviews and questionnaire. Based on the instrument, the researcher assesses teachers’ persepctive by fifteen statements. The results shows that the teachers’ has positive perspective in online English teaching at SMPN 10 Tanjungpinang.